2016
DOI: 10.1021/acs.est.6b03520
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitized Formation of Secondary Organic Aerosols above the Air/Water Interface

Abstract: In this study, we evaluated photosensitized chemistry at the air–sea interface as a source of secondary organic aerosols (SOA). Our results show that, in addition to biogenic emissions, abiotic processes could also be important in the marine boundary layer. Photosensitized production of marine secondary organic aerosol was studied in a custom-built multiphase atmospheric simulation chamber. The experimental chamber contained water, humic acid (1–10 mg L–1) as a proxy for dissolved organic matter, and nonanoic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 65 publications
2
83
0
Order By: Relevance
“…The pattern of bands at 0.9, 1.3, 1.6, 2.2, 2.4, and 2.6 ppm follows the structure elucidated by Suzuki et al (2001) and is attributed to C 7 -C 9 aliphatic dicarboxylic acids and oxo-acids. This class of organic compounds, clearly characterizing the aliphatic composition of the ambient samples in the Weddell Sea area, could originate from degraded (oxidized) lipids (Kawamura et al, 1996), or from gas-to-particle conversion of carbonyls produced by the photochemical oxidation of lipids at the air-sea interface (Bernard et al, 2016;Alpert et al, 2017). Support for the lat-ter hypothesis (secondary formation) is given by the fact that the N-osmolytes (betaine, choline) present in the sea spray generated in the tanks were completely absent in the ambient sample.…”
Section: Ambient Aerosols From the Weddell Seamentioning
confidence: 99%
“…The pattern of bands at 0.9, 1.3, 1.6, 2.2, 2.4, and 2.6 ppm follows the structure elucidated by Suzuki et al (2001) and is attributed to C 7 -C 9 aliphatic dicarboxylic acids and oxo-acids. This class of organic compounds, clearly characterizing the aliphatic composition of the ambient samples in the Weddell Sea area, could originate from degraded (oxidized) lipids (Kawamura et al, 1996), or from gas-to-particle conversion of carbonyls produced by the photochemical oxidation of lipids at the air-sea interface (Bernard et al, 2016;Alpert et al, 2017). Support for the lat-ter hypothesis (secondary formation) is given by the fact that the N-osmolytes (betaine, choline) present in the sea spray generated in the tanks were completely absent in the ambient sample.…”
Section: Ambient Aerosols From the Weddell Seamentioning
confidence: 99%
“…6 Briefly, particle formation upon oxidation of the produced VOCs was investigated using a 2 m 3 chamber made of FEP film (fluorinated ethylene propylene). The chamber was equipped with a glass reservoir at the bottom, which contained the biofilm samples, and surrounded by 12 UV-vis lamps (OSRAM lamps, 30…”
Section: 7mentioning
confidence: 99%
“…In the past, it was shown that unique photochemical reactions with significant implications for atmospheric processes can occur at such interfaces, leading to the formation of volatile organic 5 compounds (VOCs) [1][2][3][4][5] and secondary organic aerosols, 6 or acting as sinks for reactive species, such as NO 2 or ozone. [7][8][9][10] This interfacial photochemistry is exclusively due to the presence of surfactants which tend to concentrate in surface layers with respect to the underlying bulk water.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 To the best of our knowledge, a handful of studies were conducted to investigate the aqSOA formation at the air-water interfaces, suggesting its effect on global aerosol budgets. [13][14][15] Most studies were performed using either bulk solution or chamber experiments coupled with NMR, 16 ESI-MS, 17 FT-ICR-MS, 18 or DESI-MS for product detection. 19 Schweitzer proposed that surface chemistry of glyoxal protonation occurred prior to uptake by aqueous droplet like formaldehyde.…”
Section: Introductionmentioning
confidence: 99%